Segregation Analysis of Genotyped and Family-Phased, Long Range MHC Classical Class I and Class II Haplotypes in 5 Families With Type 1 Diabetes Proband in the United Arab Emirates - Tay, Guan K.; Al Naqbi, Halima; Mawart, Aurélie; Baalfaqih, Zahrah; Almaazmi, Anoud; Deeb, Asma; Alsafar, Habiba (Frontiers in Genetics, 2021)
The classical Human Leucocyte Antigen (HLA) class II haplotypes of the Major Histocompatibility Complex (MHC) that are associated with type 1 diabetes (T1D) were identified in five families from the United Arab Emirates (UAE). Segregation analyses were performed on these 5 families with the disease, 3 with one child and 2 with 2 children diagnosed with T1D. Three HLA-DR4 haplotypes were identified: HLA- DRB1*04:01:01-DQB1*03:02:01:01; HLA- DRB1*04:02:01- DQB1*03:02:01; and HLA -DRB1*04:05:01-DQB1*02:02:01:02. All have previously been identified to be associated with T1D in studies of the Arabian population. In the 10 parents from the 5 families, 9 had at least one HLA-DR4 and HLA-DR3 haplotype which potentially predisposes them to T1D. Of these 9 parents, 3 were heterozygous for HLA-DR4/HLA-DR3 and one was homozygous for HLA-DR3. Two haplotypes that were identified here extend to the HLA class I region were previously designated AH8.2 (HLA -A*26-B*08-DRB1*03) and AH50.2 (HLA -C*06-B*50-DRB1*03:01-DQ*02) and associated with diabetes in neighbouring North Indian populations. This study provides examples of MHC haplotype analysis in pedigrees to improve our understanding of the genetics of T1D in the understudied population of the UAE.